2013
DOI: 10.1021/nl304060g
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity and Phonon Transport in Suspended Few-Layer Hexagonal Boron Nitride

Abstract: The thermal conductivity of suspended few-layer hexagonal boron nitride (h-BN was measured using a micro-bridge device with built-in resistance thermometers. Based on the measured thermal resistance values of 11-12 atomic layer h-BN samples with suspended length ranging between 3 and 7.5 m, the room-temperature thermal conductivity of a 11-layer sample was found to be about 360 Wm -1 K -1 , approaching the basal plane value reported for bulk h-BN.The presence of a polymer residue layer on the sample surface w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
472
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 628 publications
(511 citation statements)
references
References 25 publications
23
472
4
1
Order By: Relevance
“…The expanding portfolio of atomic sheets illustrated in Fig. 1a currently include the archetypical 2D crystal graphene 3-14 , transition metal dichalcogenides (TMDs) 1,2,15-21 , diatomic hexagonal boron nitride (h-BN) 3,[22][23][24][25] , and emerging monoatomic buckled crystals collectively termed Xenes, which include silicene 2,26,27 , germanene 2 and phosphorene [28][29][30][31] . These materials are considered 2D because they represent the thinnest unsupported crystalline solids that can be realized, possess no dangling surface bonds and show superior intralayer (versus interlayer) transport of fundamental excitations (charge, heat, spin and light).…”
mentioning
confidence: 99%
“…The expanding portfolio of atomic sheets illustrated in Fig. 1a currently include the archetypical 2D crystal graphene 3-14 , transition metal dichalcogenides (TMDs) 1,2,15-21 , diatomic hexagonal boron nitride (h-BN) 3,[22][23][24][25] , and emerging monoatomic buckled crystals collectively termed Xenes, which include silicene 2,26,27 , germanene 2 and phosphorene [28][29][30][31] . These materials are considered 2D because they represent the thinnest unsupported crystalline solids that can be realized, possess no dangling surface bonds and show superior intralayer (versus interlayer) transport of fundamental excitations (charge, heat, spin and light).…”
mentioning
confidence: 99%
“…Taking the combined thickness of the graphene and two h-BN layers to be $30 nm, with an effective thermal conductivity of $500 W m À1 K À1 , yields a value of k of approximately 10 lm, which is consistent with the value obtained experimentally in this work. In this simple analysis, we have ignored the extra vertical thermal resistance caused by the interfaces between the different layers, and also any effect due to the possible wrinkling of the 2D materials, both of which could act to increase the thermal resistance into the substrate thus increasing k. In contrast, residues from the transfer process have been shown to decrease the lateral thermal conductivity of h-BN, 23 which would decrease the characteristic length. Although a full study of the dominant contributions to the overall thermal characteristics of the devices, including the effects of heat loss through radiation, convection, and via the contacts, is beyond the scope of this manuscript, this simple analysis highlights the potential of this architecture to be used to engineer the thermal properties of these devices to, for example, maximize the difference between the "on" and "off" temperatures of the emitting area.…”
mentioning
confidence: 99%
“…15 In addition, we have calculated R c, f for Pettes et al's bi-layer graphene sample using the κ s values reported by Sadeghi et al 18 for a supported bi-layer graphene sample in addition to the full range of g i values reported in the literature for graphene and h-BN. 19,31,[33][34][35][36] The obtained R c = R c, m + R c, f is shown in Fig. 1(c).…”
Section: -6mentioning
confidence: 95%
“…The interface heat transfer between the supported graphene segment and the support results in a hyperbolic temperature distribution in the supported graphene segment, similar to that found along a fin with the base connected to a heat source and the circumference surface exposed to a reservoir at a different temperature. 28 Hence, a fin resistance model has been developed in prior works for the calculation of the sample-support interface thermal resistance as [29][30][31][32] …”
Section: -6mentioning
confidence: 99%
See 1 more Smart Citation